Citizens of a Christian nation: Evangelical missions and the problem of race in the nineteenth century - Chang, Derek (Politics and culture in modern America, 2010)
Introduction: Evangelical Christianity and the problem of difference -- "A grand and awful time" -- Faith and hope -- Callings -- Congregation -- Conflict and community -- Conclusion: Transformations